Formal Information Flows Among Top Authorities of the Brazilian Federal Government based on Co-word Analysis of Data Published in the Official Gazette - Soares, Rafael Henrique Santos; Fernandes, Jorge H. C.; Sampaio, Ricardo (Anais do Brazilian Workshop on Social Network Analysis and Mining (BraSNAM), 2016)
This paper describes a methodology for modeling social networks of formal communications among top authorities of the Brazilian Federal Government grounded on data available in the government official gazette (Diário Oficial da União). The text of a large number of official publications such as presidential decrees, ministerial orders and authority nominations was analyzed for identification of citations to organizations and persons. The co-occurrence of names of persons in such publications created a network of relations among such persons. An ego-network was built around the president Dilma Rousseff. Metrics of social network analysis were collected and analyzed in an exploratory fashion.